2017
DOI: 10.1111/1556-4029.13571
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Method for Reassociating Human Tali and Calcanei from a Commingled Context

Abstract: In a commingled context, assessing that a talus and a calcaneus correspond to the same individual could become a primary step for accurately sorting human remains. For this purpose, the lengths and widths of the trochlea, posterior calcaneal articular surface, and posterior talar articular surface were measured in 197 individuals (105 males, 92 females) from the Athens Collection. A total of 12 highly accurate equations for reassociating tali and calcanei were developed, using simple and multiple linear regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…The ranges were proposed based on the 90% correct classification of the cases. If there is more than one potential correspondence, then a morphoscopic approach should be additionally implemented, as described in .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The ranges were proposed based on the 90% correct classification of the cases. If there is more than one potential correspondence, then a morphoscopic approach should be additionally implemented, as described in .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that osteometric sorting of commingled human remains can give promising results . Anastopoulou et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations